Evaluation of the Possible Use of the Ankara-Sivas High-Speed Railway Line for Freight Transport - Hülya Zeybek (Journal of Transportation and Logistics)
Logistics trends and the growing awareness of more sustainable transport in the global market have been a strong impetus for the growth of rail freight transport, particularly evident in the transport of time-sensitive, high-value, and capital-intensive goods. Therefore, expanded High-Speed Railway (HSR) systems provide a reliable opportunity for fast freight transport. In Turkey, the length of the HSR has reached 1,213 km and 1,889 km more are under construction, mostly dedicated to passenger transport. This research investigates the possible use of the new Ankara-Sivas HSR line for freight by analyzing the future traffic potential to find out the spare capacity for freight traffic. The results of the research reveal that the traffic potential on the Ankara-Sivas HSR line might not be justified by passenger traffic alone and the spare capacity should be used by express freight trains. Considering that Turkey is well prepared to become a Eurasian transport hub connecting Europe with Asia via the Middle Corridor, the outcome of this research may contribute to the development of suitable solutions that may improve the economic, environmental, and social sustainability of HSR systems.